2021
DOI: 10.2147/nsa.s298003
|View full text |Cite
|
Sign up to set email alerts
|

Contactless Nanoparticle-Based Guiding of Cells by Controllable Magnetic Fields

Abstract: Controlled and contactless movements of magnetic nanoparticles are crucial for fundamental biotechnological and clinical research (eg, cell manipulation and sorting, hyperthermia, and magnetic drug targeting). However, the key technological question, how to generate suitable magnetic fields on various length scales (µm–m), is still unsolved. Here, we present a system of permanent magnets which allows for steering of iron oxide nanoparticles (SPIONs) on arbitrary trajectories observable by microscopy. The movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
(24 reference statements)
0
25
0
Order By: Relevance
“…However, others previously functionalized lymphocytes with magnetic nanoparticles and showed increased therapeutic success with the adoptive transfer of T cells and NK cells [28,35]. Further, contactless magnetic movement by permanent magnets and dynamically programmable magnetic fields is under intense investigation [29,68]. Interestingly, for future translation into clinics, the magnetic field coils inherent to clinical MRI scanners can not only be used for tracking but also for steering magnetic nanoparticles or nanoparticle-loaded cells into the wanted region [23,24], possibly enabling an imagebased therapy in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, others previously functionalized lymphocytes with magnetic nanoparticles and showed increased therapeutic success with the adoptive transfer of T cells and NK cells [28,35]. Further, contactless magnetic movement by permanent magnets and dynamically programmable magnetic fields is under intense investigation [29,68]. Interestingly, for future translation into clinics, the magnetic field coils inherent to clinical MRI scanners can not only be used for tracking but also for steering magnetic nanoparticles or nanoparticle-loaded cells into the wanted region [23,24], possibly enabling an imagebased therapy in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could be shown that a combined application of IONP, cell therapy and magnetic fields can lead to a re-endothelialization and functional improvement of vessels. Precise movement of IONP-loaded cells was recently demonstrated by the use of Halbach magnets by Blümler et al [ 263 ]. Kyrtatos et al used a Halbach array-based magnet design to deliver ferumoxides-loaded EPCs to the site of arterial injury to reduce neointima formation by re-endothelialization [ 264 ].…”
Section: Cardiovascular Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…If no gradient (=neither force nor velocity) is present, cluster-formation will only happen on the time-scale of Brownian motion (i.e., selfdiffusion). Gradients will assist a quick cluster-formation as the particles are all moved in the same direction [33], and hence their inter-distances will become smaller in this direction. As soon as some larger clusters have formed, they will attract neighboring particles with increased force.…”
Section: Magnetic Force and Velocitymentioning
confidence: 99%
“…If there are sufficiently many particles in the vicinity, such clusters will form in any magnetic field and this behavior is not a particular feature of the suggested instrument. However, they can easily be studied in them macroscopically [17] and microscopically [33].…”
Section: Magnetic Force and Velocitymentioning
confidence: 99%